Long-Term Outcomes of Elagolix in Women With Endometriosis: Results From Two Extension Studies. Issue 1 (July 2018) - Surrey, Eric; Taylor, Hugh S.; Giudice, Linda; Lessey, Bruce A.; Abrao, Mauricio S.; Archer, David F.; Diamond, Michael P.; Johnson, Neil P.; Watts, Nelson B.; Gallagher, J. Chris; Simon, James A.; Carr, Bruce R.; et al.
Abstract : OBJECTIVE: To evaluate the efficacy and safety of elagolix, an oral, nonpeptide gonadotropin-releasing hormone antagonist, over 12 months in women with endometriosis-associated pain. METHODS: Elaris Endometriosis (EM)-III and -IV were extension studies that evaluated an additional 6 months of treatment after two 6-month, double-blind, placebo-controlled phase 3 trials (12 continuous treatment months) with two elagolix doses (150 mg once daily and 200 mg twice daily). Coprimary efficacy endpoints were the proportion of responders (clinically meaningful pain reduction and stable or decreased rescue analgesic use) based on average monthly dysmenorrhea and nonmenstrual pelvic pain scores. Safety assessments included adverse events, clinical laboratory tests, and endometrial and bone mineral density assessments. The power of Elaris EM-III and -IV was based on the comparison to placebo in Elaris EM-I and -II with an expected 25% dropout rate. RESULTS: Between December 28, 2012, and October 31, 2014 (Elaris EM-III), and between May 27, 2014, and January 6, 2016 (Elaris EM-IV), 569 participants were enrolled. After 12 months of treatment, Elaris EM-III responder rates for dysmenorrhea were 52.1% at 150 mg once daily (Elaris EM-IV=50.8%) and 78.1% at 200 mg twice daily (Elaris EM-IV=75.9%). Elaris EM-III nonmenstrual pelvic pain responder rates were 67.8% at 150 mg once daily (Elaris EM-IV=66.4%) and 69.1% at 200 mg twice daily (Elaris EM-IV=67.2%). After 12 months of treatment, Elaris EM-III dyspareunia responder rates were 45.2% at 150 mg once daily (Elaris EM-IV=45.9%) and 60.0% at 200 mg twice daily (Elaris EM-IV=58.1%). Hot flush was the most common adverse event. Decreases from baseline in bone mineral density and increases from baseline in lipids were observed after 12 months of treatment. There were no adverse endometrial findings. CONCLUSION: Long-term elagolix treatment provided sustained reductions in dysmenorrhea, nonmenstrual pelvic pain, and dyspareunia. The safety was consistent with reduced estrogen levels and no new safety concerns were associated with long-term elagolix use. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT01760954 and NCT02143713. Abstract : In women with endometriosis-associated pain, long-term elagolix treatment reduced dysmenorrhea, nonmenstrual pelvic pain, and dyspareunia, with a safety profile consistent with its mechanism of action.